Analisis Komposisi Anggaran Pembangunan Terhadap Pertumbuhan Pendapatan Daerah Di Kabupaten Lebak - Dede Suharna; Liesna Halimutusa; Bambang Pujo Purwoko (E-Journal Studia Manajemen, 2012)
Regional development as part of national development is essentially an effort to increase the capacity of regional growth and which will generate revenue growth areas, especially revenue. Revenue swampy district is still larger transfers from central funds as grants. Composition of the Development expenditure that budgeting is directly affected by the program or activity is expected to increase local revenue growth. Besides the fiscal decentralization brings more benefits for the regions to manage their own fiscal capacity. This study examined the impact of the composition of the development budget to the revenue growth in the district swampy area using the case study method. The population in this study is Lebak district budget with sample budget and realization of the budget year 1999-2009, a technique using linear regression analysis. This study found that the composition of the development budget has a negative impact on revenue growth. The coefficient of determination variable X does not provide significant effect on variable Y. The results of the analysis obtained by the composition of the development budget does not influence or no significant effect on local revenue growth of Lebak.